2022
DOI: 10.1002/nau.25076
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral water vapor ablation of the prostate with the Rezūm system: Urodynamic findings

Abstract: Aims The efficacy of the transurethral convective interstitial radiofrequency water vapor thermal ablation of the prostate with the Rezūm system for the treatment of male lower urinary tract symptom due to benign prostatic hyperplasia is well proven. The improvement of urodynamic parameters obtained from a simple uroflowmetry cannot measure the effect of water vapor injection on the bladder outlet obstruction. Methods This monocentric retrospective pilot study analyzes the data of pressure‐flow studies perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Whether the rate of postoperative deobstruction would have been higher if all patients had undergone repeat urodynamic testing remains speculative. Our study con rms the ndings of a previous study that reported a BOOI reduction of 53.8 cmH 2 O (12).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whether the rate of postoperative deobstruction would have been higher if all patients had undergone repeat urodynamic testing remains speculative. Our study con rms the ndings of a previous study that reported a BOOI reduction of 53.8 cmH 2 O (12).…”
Section: Discussionsupporting
confidence: 91%
“…In 2021, a randomized controlled clinical trial reported signi cant improvements in patient-related symptom relief, quality of life, and uro owmetry measurements over a 5-year follow-up period (5). Rezum has also been shown to be safe and effective in multiple retrospective studies (6)(7)(8)(9)(10)(11), but data on its effect on bladder outlet obstruction (BOO) are rare (12).…”
Section: Introductionmentioning
confidence: 99%
“…39 The BOOI was reduced by 53 in a small study of patients treated with WVTT, and a study of urodynamic outcomes following robotic water jet ablation reported comparable reductions in pdetQmax to TURP (35cmH 2 O). 40,41 However, studies on urodynamic outcomes are limited to small, retrospective series, with heterogenous outcome measures, and so prospective comparative studies with urodynamic outcomes are required. Importantly, differences in outcome may also occur with the same surgical treatment due to surgical variability.…”
Section: Urodynamic Outcomesmentioning
confidence: 99%
“…A study of 20 patients treated with PUL reported only modest relief of obstruction based on urodynamic parameters (reduction in urethral resistance factor of 15cmH 2 O) 39 . The BOOI was reduced by 53 in a small study of patients treated with WVTT, and a study of urodynamic outcomes following robotic water jet ablation reported comparable reductions in pdetQmax to TURP (35cmH 2 O) 40,41 . However, studies on urodynamic outcomes are limited to small, retrospective series, with heterogenous outcome measures, and so prospective comparative studies with urodynamic outcomes are required.…”
Section: Do All Types Bladder Outlet Surgeries Including Mists Have S...mentioning
confidence: 99%